a) (4a - 7) (3a + 4) =

b) (- 3x - 5y) (2x + 4y) =

c) (a + 3) (a - 2) +(a - 4) (a + 5) =

d) (m - 4) (5m + 3) – (2m + 3) (4 - 2m) =

e) ( x – 4)2 =

f) ( x - 2)( 3x - 5) + ( -2x + 6)=


Odpowiedź :

a) (4a - 7) (3a + 4) = 12a² + 16a - 21a - 28 = 12a² - 5a - 28

b) (-3x - 5y) (2x + 4y) = -6x² - 12xy - 10xy - 20y² = -6x² - 20y² - 22xy

c) (a + 3) (a - 2) + (a - 4) (a + 5) = - 2a + 3a - 6 + + 5a  - 4a - 20 =

= 2a² + 2a - 26

d) (m - 4) (5m + 3) – (2m + 3) (4 - 2m) = 5m² + 3m - 20m - 12 - (8m - 4m² + 12 - 6m) = 5m² + 3m - 20m - 12 - 8m + 4m² - 12 + 6m = 9m² - 19m - 24

e) (x – 4) 2 = 2x - 8

f) (x - 2) (3x - 5) + (-2x + 6) = 3x² - 5x - 6x + 10 - 2x + 6 = 3x² - 13x + 16